Keys to succesful exclusive breastfeeding / Mardhiah Ismail … [et al.] - Ismail, Mardhiah; Mohd Mydin, Marlina; Kamarullah, Shahida Hanum; Yahya, Norihan; Ramli, Noor Affeeda (2012)
Breastfeeding offers great advantages for families, mothers and also for the babies. Breastfeeding should be initiated from the time a child is born and subsequently continued for 6 month until 2 years old as clearly mentioned in the Quran. Lack of knowledge and motivation as well as easy accessibility of infant formula in market are among the factors which have caused most Muslim parents to neglect breastfeeding as a whole. In our country, breastfeeding rate is lower compared to other developed countries like America and New Zealand and the discontinuation rate is a/so high. This paper intends to explain the importance of breast feeding and the way to success in breastfeed and at the same time highlighting some of the benefits of breastfeeding from all aspects which include management of breastfeeding for working mothers.